Avaliação dos impactos do uso público em trilhas: uma metodologia baseada no estudo de uma trilha interpretativa - Parque Estadual Mata dos Godoy, Paraná - Claudia Melatti; Rosely Sampaio Archela (Confins)
Assessment of the impacts of public use on trails: a methodology based on the study of interpretative trail - Mata dos Godoy State Park, Paraná - The trails are the areas most frequented by visitors in parks, but many of them are restricted to use. The current dilemma is how to maintain environmental conservation and public visitation in protected areas without compromising the biodiversity of the site and at the same time the quality of public access. In this study, we sought to investigate the condition of a trail used by visitors in Mata dos Godoy State Park, Londrina – Paraná, to assess the possible impacts existing and visitors awareness of the conduct. The survey of the impact indicators were collected in 13 points (thirteen) of observation.A survey of 366 visits (three hundred and sixty-six) was performed during the period of May to October 2010, in order to verify the knowledge of minimum impact practices. By analyzing the state of conservation of the trails, it was found that the same remains preserved despite its use. The way it was designed to work together with environmental education has brought good results, allowing the possibility to integrate environmental conservation and public visitation.